Agroindústria canavieira no interior de São Paulo: o caso de Lençóis Paulista - Pelegrin, Rodolfo Augusto Monteiro [UNESP] (2016)
This work intends to analyze the development of the sugar cane agroindustry of Lençóis Paulista and the meanings of its activity in the territory of the municipality. This analysis takes place from the discussion of the development and its practices in the context of the Brazilian dependent capitalism, passes by the revision of the development of the sugar cane agroindustry of São Paulo and then approaches the territorial formation of Lençóis Paulista and the relationship between the sugar cane and the local reality. This movement of the study allows for the observation that the development of the agro industrial sugar cane of Lençóis Paulista is based on movements and tendencies not exclusive to its municipal limits, but common in the State of São Paulo, and under the more general influence of the Brazilian capitalism and its external determinants. The formation of the municipality is founded on movements of the colonization towards the interior in the end of the 18th century, and is consolidated with the advance of the coffee cultivation in the west of the State of São Paulo in the 19th century and the total suppression of the natives way of life in the region. Present since the beginning of the 20th century, the activity related to the sugar cane had a first moment of growth with the installation of tens of firewater distilleries. At the end of the decade of 1940, the Usina Barra Grande of Lençóis (sugar mill and later distillery) is inaugurated, and a process of productive concentration is begun, (together with policies of The State for the sugar sector), also related to increasing concentration of local power by the families owning the distilleries. The modernization headed locally by the sugar mills elite is typical, reproducing the underdevelopment and the dependency, founded on a history of genocide of the native populations, deliberate predation of the environment and of the natural resources, and in the intense exploitation of labor, either in the form of forced labor or through wages.